Green roads ahead: a critical examination of bio-bitumen for sustainable infrastructure - Zhang, Yan; Ding, Pan; Zhang, Ling; Luo, Xiangyu; Cheng, Xu; Zhang, Hongfei (Frontiers in Materials, 2024)
Non-renewable nature and continuously increased consumptions of bitumen is a serious challenge for the development of infrastructure, especially for the constructions and maintenances of asphalt pavements. To cope with this situation, some sustainable strategies are needed. Extensive efforts have been made to improve the resilience, sustainability and circularity of asphalt pavements. Among them, the utilisation of bio-based materials is one of the most promising measures. This paper systemically reviewed the state-of-the-art knowledge in the development of bio-bitumen. Woodbased oils, waste cooking oils and manure-based bio-bitumen were selected as the review objectives. It was revealed that all bio-based oils currently being used are more suitable for serving as additives like softeners, rejuvenators, or modifiers rather than as alternative of binders. One of the most promising utilisations of bio-oils is as rejuvenators, potentially antioxidants as well. Incorporating polymers with bio-oils is another feasible practice to improve the performance of bio-bitumen. Causation should be taken when producing bio-based bitumen since compatibility might have some kind of influence on the performance and this issue should be addressed carefully.